The host in the machine : examining the digital in the social - Thomas-Jones, Angela (Chandos internet series., 2010)
Navigating the social within the digital can be a contentious undertaking, as social networks confuse the boundary between offline and online relationships. These systems work to bring people together in an online environment. Participation can dislocate users from other relationships, however, and deviant 'online' behaviour can create 'offline' issues. This text tackles online social networks, by navigating these systems from the birth to the death of the digital self. The author begins by examining the creation of a virtual identity in online networks popularized by websites such as Facebook and Myspace. The book subsequently explores how the social self is intrinsic to how social, cultural and professional relationships are discovered, forged and maintained. The text journeys through the popular criticisms of social networking such as employee time-wasting, bullying, stalking, the alleged links between social networks and suicide and the decline of a user's public image.